2020
DOI: 10.1002/hpja.313
|View full text |Cite
|
Sign up to set email alerts
|

Validity of self‐reported anthropometrics in Arabic‐speaking adults in Australia

Abstract: Issue addressed Body mass index (BMI) is generally accepted as a useful measurement for monitoring risk factors in adults. Although self‐reported anthropometric measurements are deemed to be more cost‐effective, its accuracy has been debated. While BMI based on self‐reported measures may have to be relied on, accuracy of reporting such measures among culturally and linguistically diverse groups is unknown. Methods Face‐to‐face surveys were conducted among 272 adults of Arabic‐speaking backgrounds living in sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The findings of our study should be considered with caution given our sample size and should be verified in future studies using larger samples. We acknowledge that our sample size (n ¼ 167) was smaller than that of studies participants in the general population (e.g., n ¼ 272, Arjunan et al, 2019). In addition, our participants were aware that they were going to be measured for actual height and body mass subsequent to completing questionnaires on which they self-reported these variables; this knowledge may have influenced the degree of bias they expressed, perhaps helping to explain a smaller bias in this sample than in studies with participants in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of our study should be considered with caution given our sample size and should be verified in future studies using larger samples. We acknowledge that our sample size (n ¼ 167) was smaller than that of studies participants in the general population (e.g., n ¼ 272, Arjunan et al, 2019). In addition, our participants were aware that they were going to be measured for actual height and body mass subsequent to completing questionnaires on which they self-reported these variables; this knowledge may have influenced the degree of bias they expressed, perhaps helping to explain a smaller bias in this sample than in studies with participants in the general population.…”
Section: Discussionmentioning
confidence: 99%
“…The use of self-reported measures based on recall or estimation of body size has been validated [ [53] , [54] , [55] , [56] , [57] ] for use when direct measurements are not possible. It has been shown that the gap between the BMI calculated from body measures obtained directly by the health professional and from self-reported measures by recall has only a mild influence on the clinical evaluation of the patient performed by the professional [ 36 ], reinforcing the potential for their use in the remote assessment when direct measurements cannot be taken.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, self-reported measures must be adopted sparingly due to the inherent limitations and risks of error [ 53 , [57] , [58] , [59] , [60] , [61] ], especially when the goal is to assess changes over time. In general, reporting estimated height tends to be more difficult than weight, especially by adults and the elderly of low resource settings, as their body size is not frequently measured in health services and this could undermine recollection.…”
Section: Discussionmentioning
confidence: 99%